Abnormal grain coarsening in cyclically deformed gradient nanograined Cu. (1st March 2018) - Long, J.Z.; Pan, Q.S.; Tao, N.R.; Lu, L.
Abstract: Microstructural evolution of gradient nanograined (GNG) Cu was investigated under strain-controlled cyclic deformation. Mechanically driven abnormal grain coarsening initiated from the ultrafine grained subsurface layer and eventually extended to the nanograined top surface with increasing cycles. Abnormal grain coarsening and the formation of dislocation patterns sustain the cyclic plastic strain and postpone the formation of extrusions/intrusions at the top surface, contributing to the enhancement of overall cyclic properties of GNG Cu. Graphical abstract: